An Application of Four Sanghawatthu for Human Resource Management of Hotel Establishment in Bang Lamung District Chonburi Province - Jadjantuek , Phakhawasita; Suwannawong, Benjamas; Rakkhitadhammo, Phamaha (Journal of Dhamma for Life, 2025)
This research has the objectives are 1) to study about the principles of Four Sanghahavatthu in Theravada Buddhism, 2) to study about the condition issues of human resource management of hotel establishments in Bang Lamung District Chonburi Province, 3) to study about an application of Four Sanghahavatthu for human resource management of hotel establishments in Bang Lamung District Chonburi Province. This research is qualitative research. The research result is found that The principles of Four Sanghahavatthu in Theravada Buddhism is a principle that encourage good relationships and unity in society. For human resources management in many areas such as recruitment, training and operation; applying the 4 Sanghahavatthu can solve these issues by encourage providing the knowledge and skills, polite speech, helpful and participation that leads to good relationship, happiness in the workplace and success in the organization. The condition issues of human resource management of hotel establishments in Bang Lamung District Chonburi Province; caused by management deficiencies as a result in the new employees being unable to perform to their full potential, leading to frequent resignations. The issues were also found in recruitment (few applicants), training (neglect of employee diversity), and performance (lack of in-depth training), resulting in employees being unable to perform their duties effectively. An application of Four Sanghahavatthu for human resource management of hotel establishments in Bang Lamung District Chonburi Province such as 1) Dāna; encouraging the knowledge and skills, sharing the sources and creating the equitable welfare, 2) Piyavaja; emphasizing the politely and creative communication, hearing the opinions and creating a good working environment, 3) Atthajariya; supporting the benefits for employees, encouraging team-work and the development of personnel potential, 4) Samanatta; creating equality and justice, hearing the issues, requirement of the employees and create reliability, potential to enhance employee engagement, increase work efficiency, and creating sustainability for hotel establishments in a context of increased competition. Applying the principles of Dhamma to organizational management is therefore an interesting approach for the new executives in creating the happy and sustainable organizations.